Spontaneous Ureteral Rupture Diagnosis and Treatment. (23rd December 2013) - Pampana, E.; Altobelli, S.; Morini, M.; Ricci, A.; D'Onofrio, S.; Simonetti, G.
Abstract : Rupture of the urinary collecting system associated with perinephric or retroperitoneal extravasation of the urine is an unusual condition and it is commonly associated with renal obstructing disease. Perforation could occur at any level from the calix to the bladder but it is usually seen at the fornices and upper ureter. It may lead to several serious consequences including urinoma, abscess formation, urosepsis, infection, and subsequent irreversible renal impairment. We report a case of a 69-year-old woman who presented at the emergency department of our institution with severe abdominal pain. Due to symptomatology worsening, complete laboratory evaluation was performed and the patient underwent abdominal contrast enhanced computed tomography (CT) evaluation which showed contrast agent extravasation outside the excretory system without any evidence of renal calculi at basal acquisition. It was decided to perform a double-J stent placement which was followed by complete healing of the ureter and its removal was performed 8 weeks later. Diagnosis and therapeutic approaches are discussed.